The visit of an all-party group of Members of Parliament to Spain : report - Crawford Greene, W. P. ; Grenfell, D. R. (David Rhys), 1881-1968 ; James, A. W. ; Macnamara, J. R. J. ; Roberts, Wilfrid
1936-08-27 014_0007_014 292/946/14/7(xiv)